2014
DOI: 10.1186/2051-4190-24-14
|View full text |Cite
|
Sign up to set email alerts
|

Man is not a big rat: concerns with traditional human risk assessment of phthalates based on their anti-androgenic effects observed in the rat foetus

Abstract: Phthalates provide one of the most documented example evidencing how much we must be cautious when using the traditional paradigm based on extrapolation of experimental data from rodent studies for human health risk assessment of endocrine disruptors (EDs). Since foetal testis is known as one of the most sensitive targets of EDs, phthalate risk assessment is routinely based on the capacity of such compounds to decrease testosterone production by the testis or to impair masculinization in the rat during foetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 134 publications
2
21
0
1
Order By: Relevance
“…This paper highlights the need of rigorous comparisons of EDC hazards in human and rodent models in agreement with our previous warning (56,57).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This paper highlights the need of rigorous comparisons of EDC hazards in human and rodent models in agreement with our previous warning (56,57).…”
Section: Resultssupporting
confidence: 74%
“…We recently partly elucidated these species-specific discrepancies by comparing the direct effect of BPA on fetal Leydig cell function in rat, mouse, and human testis explants. With the use of an organotypic culture system (fetal testis assay [FeTA]) that we developed previously (55)(56)(57), we demonstrated that concentrations of BPA as low as 10 nmol/L (2.28 ng/mL) reduce the fetal Leydig cell-specific functions in human fetal testes, but at least 100-fold higher concentrations are required in mouse and rat testes (58).…”
Section: Bpa Affects Fetal Testis Developmentmentioning
confidence: 98%
“…Animal models are critical in deciphering the complex mechanisms underpinning the effects of EDCs despite concerns that not all findings observed in animals extrapolate faithfully to humans (Habert et al ., ,b). Di(2‐ethylhexyl) phthalate (DEHP) is a plasticizer used in industry to alter the properties of polyvinyl products.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this paradoxical response of mouse FLCs to prenatal exposure to phthalates, INSL3 expression was shown to be suppressed in these steroidogenic cells after exposure to DEHP in utero [14]. Thus, these in vivo findings indicate that phthalates exert pro- or normoandrogenic effects on mouse FLC steroidogenesis [15,16,17]. …”
Section: Effects Of Phthalates On Mouse Leydig Cell Steroidogenesismentioning
confidence: 99%